Biodiversity and antibiotic resistance of bacteria isolated from tap water in Wrocław, Poland - Leginowicz, Monika; Siedlecka, Agata; Piekarska, Katarzyna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Microbial contamination and biodiversity were determined for the drinking water samples collected from selected points of the water supply system in Wrocław, Poland. All tested samples met the requirements of Polish law, i.e., the Regulation of the Minister of Health. However, the antibiotic resistant bacteria were found. The correlation between the distance of sampling points from water treatment plants and their microbial contamination was not established. Nevertheless, the Na Grobli treatment plant seemed to produce water of higher microbial quality than the Mokry Dwór treatment plant at the moment of sampling. The identification of representative isolates was performed with 16S rRNA gene sequencing and MALDI-TOF mass spectrometry and the results of these two methods were compared, indicating some discrepancies. Nevertheless, bacteria dwelling in drinking water in Wrocław belonged to the phyla Actinobacteria, Proteobacteria (α-, β-, γ-Proteobacteria) and Firmicutes. The determination of antibiotic resistance profiles showed that 12 from 17 tested isolates revealed resistance to at least one antibiotic and two strains were multi-drug-resistant.Microbial contamination and biodiversity were determined for the drinking water samples collected from selected points of the water supply system in Wrocław, Poland. All tested samples met the requirements of Polish law, i.e., the Regulation of the Minister of Health. However, the antibiotic resistant bacteria were found. The correlation between the distance of sampling points from water treatment plants and their microbial contamination was not established. Nevertheless, the Na Grobli treatment plant seemed to produce water of higher microbial quality than the Mokry Dwór treatment plant at the moment of sampling. The identification of representative isolates was performed with 16S rRNA gene sequencing and MALDI-TOF mass spectrometry and the results of these two methods were compared, indicating some discrepancies. Nevertheless, bacteria dwelling in drinking water in Wrocław belonged to the phyla Actinobacteria, Proteobacteria (α-, β-, γ-Proteobacteria) and Firmicutes. The determination of antibiotic resistance profiles showed that 12 from 17 tested isolates revealed resistance to at least one antibiotic and two strains were multi-drug-resistant.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 85-98
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma